Experimental investigation of an improved version of the four-step magnesium-chlorine cycle - Ozcan, Hasan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this paper, an experimental study is undertaken to capture HCl in dry form in order to decrease the power consumption of the four-step Mg-Cl cycle using MgO as the capturing agent. A new experimental method is developed to capture HCl from its mixture with steam, and liberate HCl in a dry form. Several cases are studied to observe HCl capture performance, including testing of the resulting substances in detail using Thermogravimetric Analysis (TGA), and X-ray diffraction (XRD) tests. The results of these experiments show 30.8% HCl capture by solid MgO particles in a semi-batch packed bed reactor design with an uncertainty value of 1.17%. The XRD results indicate that an optimum reactor temperature similar to 275 degrees C is critical to prevent the process from side reactions and undesired products. The experimental results are adapted to the four-step Mg-Cl cycle to form a final design with HCl capture. (c) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Mg-Cl cycle; Hydrogen production; Hybrid cycle; Thermochemical cycle; HCl capture; HOT FLUE-GASES; HYDROGEN-PRODUCTION; HCL; PREDICTION; ABSORPTION; LIMESTONE; SYSTEM; Chemistry; Electrochemistry; Energy & Fuels